The Network Level Needed in Determining Organizational Structure - Kavadarli, Altin (Information Management and Business Review, 2017)
As the external operations of organizationsbecome more complex with increasing globalization and as structures encounter difficulties in multi-tasking and increased information flow management, there is a need for more flexible and faster way of organizing. In order to promote efficiency and flexibility, organizations’ restructuring efforts result from need for coordination and work that increasingly occurs through informal networks of relationships rather than through formal structures. As the rapid adoption of social media and mobile computing are transforming how organizations in all industries relate to their environment, organizationalnetworks can be found inside every business and shape how employees share, communicate and collaborate at the workplace. New structures are emerging that blend different types of networks and hierarchies. The nature and complexity of the business determines the best the way its organizational structure is organized and this paper presents a theoretical model to help determine ideal organizational structures for different needs in order to deal with the pace and ambiguity of the business environment.